The importance and prevalence of allopolyploidy in Aotearoa New Zealand. Issue 2 (2nd April 2020) - Behling, Anna H.; Shepherd, Lara D.; Cox, Murray P.
ABSTRACT: Allopolyploids arise when two or more species hybridise to form an entirely new species with a duplicated genome. Although initially met with an array of potentially catastrophic challenges triggered by the combination of two diverged parental subgenomes within a single cell, countless allopolyploids worldwide demonstrate exceptional biological resilience by not only living under these unique circumstances, but thriving. The archipelago of Aotearoa New Zealand is home to an unexpectedly large number of allopolyploid species, both indigenous and introduced. Here, we review the prevalence and importance of these species from a local perspective. The benefits of allopolyploid species permeate multiple facets of life in New Zealand, from pastoral health and arable crop yield, to long-established viticulture and brewery practices, to the intrinsic nature of the land through the presence of diverse native allopolyploid flora. Consequently, the motivation behind the pursuit of New Zealand's allopolyploid research extends beyond improvement of the global knowledgebase and also aims to drive tangible economic and cultural impacts on the country and the lives of its people.